Labour Geographies of Workplace Restructuring: An Intra‐Labour Analysis. Issue 2 (27th October 2018) - Warren, Andrew
Abstract: Informed by labour geography's thrust to situate workers as active subjects of analysis, this article examines lived experiences of restructuring at Australia's single largest industrial workplace. Drawing on extended ethnographic research, the article traverses three restructuring outcomes faced by workers and their families: (1) job retention; (2) redundancy; and (3) re‐employment. Amid the turbulence and uncertainty of a major workplace restructuring episode, workers' different lived experiences illuminate uneven intra‐labour power relations. As capitalist workplaces are re‐organised and labour processes redefined, more conflictual and divisive relationships often develop among groups of workers differentially positioned within the hierarchical labour markets of large firms. Emphasising restructuring episodes as generative contexts for grounded labour geographies research, the article develops intra‐labour agency as a critical analytical frame to explore more deeply the agency implications of workplace structures, co‐worker relationships, and social life matters that shape workers' capacities for action inside and beyond workplaces.